Estudio de factibilidad para determinar la viabilidad de la creación de un supermercado, en el Cantón Buena Fe, provincia de los Ríos - Pilligua Pilligua, Maricela Geoconda (2013)
In Ecuador, the supermarket chains are mostly located in Quito and Guayaquil, now you are settled in Canton Good Faith According to research 40% of total household consumption of Ecuador is served by supermarkets, 30% by popular markets and about 25% by neighborhood stores, street markets, wineries and micro-markets. The company's goal is to offer quality products and maintain comprehensive care in the toilet and give customers the best alternative for purchasing household products of high quality at a reasonable price, primarily focused on meeting the needs and welfare of our customers, helping to improve their quality of life. The feasibility analysis has revealed that for 90% of staff surveyed, the company needs a steady stream of data and accurate. According to 95%, the main purpose of accounting is to prepare quality information. The 77.69% believe that the creation and establishment of a supermarket will reduce the costs of the products they consume. For 80.05%, Good Faith does not have the perfect supermarket to meet consumer demand. 95.01% for the inhabitants of Buena Fe, this county should have a modern supermarket with all services. According to 88.45% of the respondents, they would be willing to make purchases of goods if there was a modern supermarket. In this project the following results were obtained: NPV + USD 1226275.71, Internal Rate of Return: 55.17%, benefit cost ratio: 1.08 and previous Payback: 2 years, 1 month, confirming the viability of the investment.